2021
DOI: 10.1186/s12862-021-01872-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of transcriptional control of antigenic variation and virulence in human and ape malaria parasites

Abstract: Background The most severe form of human malaria is caused by the protozoan parasite Plasmodium falciparum. This unicellular organism is a member of a subgenus of Plasmodium called the Laverania that infects apes, with P. falciparum being the only member that infects humans. The exceptional virulence of this species to humans can be largely attributed to a family of variant surface antigens placed by the parasites onto the surface of infected red blood cells that mediate adherence to the vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…With respect to the SMS model, var2csa displays the properties of a sink node, and is by far the most likely var gene to become highly activated in our cultures ( Figure 3A ). This gene also displays several other properties that make it an atypical member of the family, including universal conservation extending to related species that infect chimpanzees and gorillas ( Zilversmit et al, 2013 ; Gross et al, 2021 ) and the presence of a unique upstream regulatory region that includes an upstream open reading frame (uORF) resulting in translational repression of the mRNA ( Amulic et al, 2009 ; Bancells and Deitsch, 2013 ; Chan et al, 2017 ). The gene can therefore transcribe mRNA without producing PfEMP1 and thus could be transcriptionally activated repeatedly over the course of an infection without generating an antibody response by the host.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the SMS model, var2csa displays the properties of a sink node, and is by far the most likely var gene to become highly activated in our cultures ( Figure 3A ). This gene also displays several other properties that make it an atypical member of the family, including universal conservation extending to related species that infect chimpanzees and gorillas ( Zilversmit et al, 2013 ; Gross et al, 2021 ) and the presence of a unique upstream regulatory region that includes an upstream open reading frame (uORF) resulting in translational repression of the mRNA ( Amulic et al, 2009 ; Bancells and Deitsch, 2013 ; Chan et al, 2017 ). The gene can therefore transcribe mRNA without producing PfEMP1 and thus could be transcriptionally activated repeatedly over the course of an infection without generating an antibody response by the host.…”
Section: Resultsmentioning
confidence: 99%
“…The location of a large proportion of the var gene family within subtelomeric regions makes them uniquely subject to frequent recombination and deletion events, an inherent plasticity that is reflected in the variable number of var genes observed in the genomes of different parasites isolates (55). Interestingly, despite the hyper-recombinogenic nature of the subtelomeric region in which it resides, var2csa remains conserved in all P. falciparum lines examined, and this conservation extends to the related species P. reichenowi and P. praefalciparum (35). We hypothesize that its role in mediating expression switching selects for its preservation within the genomes of wildtypes parasites.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the SMS model, var2csa displays the properties of a sink node, and is by far the most likely var gene to become highly activated in our cultures (Figure 3A). This gene also displays several other properties that make it an atypical member of the family, including universal conservation extending to related species that infect chimpanzees and gorillas (34,35) and the presence of a unique upstream regulatory region that includes an upstream open reading frame (uORF) resulting in translational repression of the mRNA (36)(37)(38). The gene can therefore transcribe mRNA without producing PfEMP1 and thus could be transcriptionally activated repeatedly over the course of an infection without generating an antibody response by the host.…”
Section: The Var2csa Locus Is Required For Efficient Var Gene Switchingmentioning
confidence: 99%
“…The majority of the var gene family is subject to frequent recombination, resulting in the gene family displaying tremendous sequence diversity when the repertoire of var genes from different isolates are compared. However, two genes, referred to as var1csa and var2csa , appear to be conserved in all P. falciparum isolates from around the world and are also found in the related Plasmodium species that infect chimpanzees and gorillas ( Otto et al, 2018b ; Gross et al, 2021 ). It has been suggested that these genes could serve an additional function as conserved regulatory elements for coordinating mutually exclusive expression ( Mok et al, 2008 ; Ukaegbu et al, 2015 ).…”
Section: Mutually Exclusive Expression In Parasites: Antigenic Variationmentioning
confidence: 99%
“…Using both FISH (Figueiredo et al, 2002;Duraisingh et al, 2005) and Hi-C (Ay et al, 2014), var genes in P. falciparum have been shown to cluster in specific nuclear compartments, with the active var gene being separated from the silent loci, but no specific genetic elements have been connected to this clustering. As previously mentioned, there are two var genes, var1csa and var2csa, that are uniquely conserved amongst all isolates of Plasmodium falciparum, and this conservation extends to related species that infect chimpanzees and gorillas (Gross et al, 2021). This is in stark contrast to the highly polymorphic sequences of all other var genes, leading to speculation that these two genes could play a role in organization of the family or by directly regulating transcription (Mok et al, 2008;Ukaegbu et al, 2015).…”
Section: Master Genetic Elementsmentioning
confidence: 99%